Paternalistic Leadership in Law Firm: Indicators of Success and Implementation - Susanto, Primadi Candra; Parmenas, Naik Henokh; Febrian, Wenny Desty; Sani, Indra; Tannady, Hendy; Suryawan, Ryan Firdiansyah (Dinasti Research, 2023)
The research objectives on paternalistic leadership can vary from understanding the concept to practical application in qualitatively different organizational contexts. This study used a qualitative research approach by researchers. Qualitative methods are basically exploratory research techniques used to investigate causes, viewpoints, and opinions to answer research questions. The choice of this qualitative research approach is appropriate. Data collection for this study will be carried out from primary and secondary data sources. Researchers collect primary data to answer research questions through reviews of scientific papers, journals, books, websites, and blogs used in the study. Paternalistic leadership in law offices is that this method has the possibility to improve employee well-being and overall organizational performance. By paying attention to the balance between authority and concern for employees, paternalistic leadership creates a supportive and motivating work environment. Assessment of success such as employee satisfaction, retention, and productivity becomes important in assessing the positive impact of paternalistic leadership. Overall, the study confirms that paternalistic leadership has a significant positive impact in the law office context, and by implementing appropriate strategies, organizations can optimize the benefits of this approach to achieve their goals and improve employee well-being.